Healthcare fraud : auditing and detection guide - Busch, Rebecca S. (Finance professional collection, 2012)
"This second edition provides comprehensive guidance on auditing and fraud detection for healthcare providers and company healthcare plans. New chapters have been added covering a comprehensive auditing model developed by the author on all of the key elements that must be addressed: Primary Healthcare, Secondary Healthcare, Information/Data Management and Privacy, Damages/Risk Management, and transparency. In addition to six new chapters, the current edition material will all be updated and brought up to date"--Provided by publisher